Reliabilism and contemporary epistemology : essays - Goldman, Alvin I., 1938- (Oxford : Oxford University Press, 2012)
This is an up-to-date collection of essays by the leading proponent of process reliabilism, refining and clarifying that theory and critiquing its rivals. The volume features important essays on the internalism/externalism debate, epistemic value the intuitional methodology of philosophy, and social epistemology.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Knowledge, Theory of; Justification (Theory of knowledge); Social epistemology